Cytomegalovirus mismatch still negatively affects patient and graft survival in the era of routine prophylactic and preemptive therapy: A paired kidney analysis. Issue 2 (14th December 2018) - Leeaphorn, Napat; Garg, Neetika; Thamcharoen, Natanong; Khankin, Eliyahu V.; Cardarelli, Francesca; Pavlakis, Martha
Abstract : The impact of cytomegalovirus (CMV) serostatus on kidney transplant outcomes in an era when CMV prophylactic and preemptive strategies are used routinely is not clearly established. Using United Network for Organ Sharing/Organ Procurement and Transplantation Network data, recipients with first deceased donor kidney transplant (≥18 years, 2010‐2015) were stratified into 4 groups in the main cohort: CMV‐seronegative donor (D−)/CMV‐seronegative recipient (R−), CMV‐seropositive donor (D+)/R−, D+/CMV‐seropositive recipient (R+), and D−/R+. In a paired kidney cohort, we identified 2899 pairs of D− kidney transplant with discordance of recipient serostatus (D−/R− vs D−/R+) and 4567 pairs of D+ kidney transplant with discordance of recipient serostatus (D+/R− vs D+/R+). In the main cohort, D+/R− was associated with a higher risk of graft failure (hazard ratio [HR] = 1.17, P = .01), all‐cause mortality (HR = 1.18, P < .001), and infection‐related mortality (HR = 1.38, P = .03) compared with D−/R−. In the paired kidney analysis, D+/R− was an independent risk factor for all‐cause mortality (HR = 1.21, P = .003) and infection‐related mortality (HR = 1.47, P = .04) compared with D+/R+. No difference in graft loss between D+/R− and D+/R+. CMV mismatch is still an independent risk factor for graft loss and patient mortality. The negative impact of D+/R− serostatus on mortality persists after fully matching for donor factors. Abstract : Using United Network for Organ Sharing data and the paired kidney analysis, Leeaphorn et al demonstrate that cytomegalovirus donor‐positive/recipient‐negative status is still an independent risk factor for mortality and graft failure in the current era where guidelines for cytomegalovirus prevention are widely implemented.